Leadership productivity model: Evaluation of operationalisation - Thomas Dobbelstein (Journal of Applied Leadership and Management, 2018)
Research questions: To what extent does the operationalisation of the Leadership Productivity Model fulfill the approved scientific quality criteria? Methods: After identifying suitable quality criteria, they were evaluated based on 1,267 questionnaires following the Leadership Productivity Survey (LPS). Dimensions as well as their criteria evaluated by applying e.g. Cronbach's Alpha, item difficulty index, correlation and factor analysis. Results: Apart from very few limitations objectivity is good. Reliability for the en-tire LPS is excellent; the reliability coefficients for each dimension are good. Criterion validity is confirmed, construct validity cannot be con-firmed by Pearson's correlation coefficients, but partly by factor analysis. Summing up the LPS is an objective, completely reliable and partially valid instrument.
Keywords: 650